O LÚDICO NO ENSINO DE FÍSICA: ELABORAÇÃO E DESENVOLVIMENTO DE UM MINICONGRESSO COM TEMAS DE FÍSICA MODERNA NO ENSINO MÉDIO - FILGUEIRA, Sérgio Silva (2009)
In this work are showed results of research with students from third grade of a public school in de high school level, in the Goiânia city. Are presented the preparation and development of a minicongress with modern physics themes. The themes were worked: photoelectric effect, wave-particle duality, nuclear fission and fusion, universe s origin, relativity theory , x-rays and laser. The classrooms were divided into groups; each was responsible for one of the topics. The objective was to write a paper to minicongress a held at the school, following all the rites of an academic scientific congress. Among the submission of paper and presentation of posters, the teacher mediate in the groups, providing them various articles and texts that had relationship with themes. The aim was to investigate the feasibility of working with themes of modern physics and contemporary at this level of education through a play activity. It is discussed in this work to the playful connection with the inclusion of topics in modern physics and Contemporary in basic school. The results showed high involvement and interest of students by the activity. It was clear the enthusiasm that students demonstrated with the themes, especially in learning the concepts involved in physical technological applications that they already knew. The elaboration of minicongress made in the school's computer laboratory. This aspect contributed to making the activity more fun, because use of computers became more conceptual discussions pleasant. The work groups were sent by another tool for evaluating the learning of concepts worked. A comprehensive analysis of search results in shows that working with themes of modern physics and contemporary in high school using the tool as playful, is a viable alternative.